ILMU JIWA FALSAFI BERBASIS AL-QUR’AN SEBAGAI SUATU DISIPLIN ILMU: SUATU TAWARAN DISIPLIN ILMU - Cipta Bakti Gama (Sekolah Tinggi Agama Islam Sadra, 2022)
Studying multiple dimensions of the human self requires an integration-interconnection between rational, scriptural, Sufistic, and empirical disciplines of knowledge. Many muslim psychologists have long developed an integrative study known as Islamic Psychology. Such integration pivots on Modern Psychology as an empirical discipline (science) which absorbs various Islamic studies on human soul, mind, behavior, and the like, so that there is still room for integration focused on philosophical and scriptural disciplines. This paper contains the initial ideas of constructing a discipline of knowledge on the human self that pivots on the integration between Islamic Philosophy and Quranic Exegesis, which is called Qur’anic-Philosophical Psychology. The findings of this paper include the formulation of a number of principles as the Basic Structure of Knowledge underlying the Quran-Based Philosophical Psychology, which is based on the idea of Logic about the components of knowledge and the idea of the Philosophy of Science about the relationship between disciplines and their social aspects.